Politeness and Impoliteness Strategies of IG Netizens’ Comments on the Government Policy on Restrictions towards Community Activities (PPKM) - Hendar; Adiandini, Nabila; Sarita, Yuli; Vawana, Ghina; Anjani, Maulati Zahrawi; Simanjuntak, Sela Febryanti (CENTRAL ASIA AND THE CAUCASUS, 2022)
Indonesians is well-known for being friendly and polite as a cultural feature of eastern people in speaking. This research aims at investigating how much the netizens use politeness and impoliteness strategies and determining what types of politeness and impoliteness strategies they use in response to the government's official stance on community activity restrictions (PPKM) due to the Covid-19 outbreak in President’ official Instagram. The method used in this qualitative research is the descriptive method aimed at giving a systematic, factual, and accurate description of language phenomena that happened in our society and represented in language use in social media, Instagram. The sample date of this research consists of 100 pros and cons of netizens’ comments on the government's policies regarding the implementation and extension of PPKM from stages 1 to 4 applied to Java and Bali Islands. Those data are then analyzed, classified, and coded based on the theories of politeness by Brown and Levinson and impoliteness by of Culpeper. The results of the research show that from the 100 obtained data on netizens’ comments on presidential decree dealing with the implementation or extension of the PPKM program from stage 1 to 4, they used 2 main strategies i.e. politeness strategies (77%) and impoliteness strategies (23%), and the types of politeness strategies used are follows 7 data (9%) on bold-on record strategy, 41 data (53%) on positive strategy, 9 data (12%) on negative strategy, and 20 data (26%); whereas, the types of impoliteness strategies used are 9 (39%) data on bold-on record impoliteness strategies, 4 (18%) data on positive impoliteness strategies, 4 (17%) negative impoliteness strategies, 6 (26%) data on Sarcasm / Mock impoliteness strategies, and 0 (0%) data on withholding and off-record impoliteness strategies.